Influence of bisphosphonates on the adherence and metabolism of epithelial cells and gingival fibroblasts to titanium surfaces - Basso, Fernanda Gonçalves [UNESP]; Pansani, Taisa N. [UNESP]; Soares, Diana G. [UNESP]; Cardoso, Lais M. [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2018)
Objectives: To evaluate the effects of sodium alendronate (SA) and zoledronic acid (ZA), on the adhesion and metabolism of epithelial cells and gingival fibroblasts to titanium surfaces considering cell functions related to an effective mucosal barrier around the implant. Materials and methods: Cells were seeded onto titanium discs and incubated for 24 h. Then, serum-free DMEM containing selected bisphosphonates (0, 0.5, 1, or 5 μM) was added for 24 and 48 h. Factors related to the achievement of an effective mechanical and immunological barrier—cell adhesion, viability, collagen epidermal growth factor, and immunoglobulin synthesis—were evaluated. Data were analyzed by Kruskal-Wallis and Mann-Whitney tests as well as by ANOVA and Tukey’s tests, (α = 0.05). Results: The presence of bisphosphonates culminated in lower cell adhesion to the titanium discs, particularly for SA at 5 μM (40%) and ZA at all concentrations (from 30 to 50%, according to increased concentrations). Reduced cell viability occurred after exposing these cells to ZA (40%); however, only 5 μM SA-treated cells had decreased viability (30%). Reduced synthesis of growth factors and collagen was observed when cells were reated with ZA (20 and 40%, respectively), while about 70% of IgG synthesis was enhanced. Conclusion: Bisphosphonates negatively affected the adhesion and metabolism of oral mucosal cells, and this effect was related to the type of bisphosphonate as well as to concentration and period of treatment. Clinical relevance: The negative effects of bisphosphonates on oral mucosal cells can hamper the formation of an effective biological seal in osseointegrated implants.
Keywords: Bisphosphonate; Connective tissue biology; Fibroblast; Implantology